Wearing a cap, thermoregulation, and thermal sensation during running in a hot environment - Wimer, G. S. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM. The aim of this study was to determine if wearing a cap negatively alters thermoregulation or thermal sensation during prolonged running in the heat. METHODS: Nine well-trained runners ran for 1 hour at 67% VO2max in a hot environment (Ta =31 °C, RH=41%) wearing (CAP) or not wearing (NOCAP) a white cotton/polyester running cap. During both running trials, subjects consumed 2 mL/kg of cold water every 15 minutes. Thermal balance was assessed using rectal (Tre) and skin temperatures (-Tsk) as well as measurement of whole-body sweat loss and thermal sensation of the head and of the overall body (8-point scale). RESULTS: There were no significant differences in Tre, -Tsk or whole-body sweat loss between conditions. When compared to NOCAP, forehead skin temperature increased more during CAP (P<0.05). Although there were no differences in ratings of thermal sensation of the overall body between treatments, ratings of thermal sensation of the head were higher (P<0.05) during CAP. There were no differences in heart rate or rating of perceived exertion between conditions. CONCLUSIONS. Despite higher ratings of thermal sensation of the head and higher forehead skin temperatures when wearing a cap during prolonged running in the heat, thermoregulation was not otherwise negatively altered.